1985
DOI: 10.1126/science.2932798
|View full text |Cite
|
Sign up to set email alerts
|

Control of Directionality in Lambda Site Specific Recombination

Abstract: The simple relation between the substrates and products of site-specific recombination raises questions about the control of directionality often observed in this class of DNA transactions. For bacteriophage lambda, viral integration and excision proceed by discrete pathways, and DNA substrates with the intrinsic property of recombining in only one direction can be constructed. These pathways display an asymmetric reliance on a complex array of protein binding sites, and they respond differently to changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 44 publications
(37 reference statements)
9
98
0
1
Order By: Relevance
“…3A) (16). The phenotypes of these ''ten'' mutants were consistent with earlier deletion studies (21,22) and showed that the P1 but not the P2 site is required for integrative recombination. Concomitantly, the P2 site but not the P1 site is required for excisive recombination.…”
Section: Resultssupporting
confidence: 76%
“…3A) (16). The phenotypes of these ''ten'' mutants were consistent with earlier deletion studies (21,22) and showed that the P1 but not the P2 site is required for integrative recombination. Concomitantly, the P2 site but not the P1 site is required for excisive recombination.…”
Section: Resultssupporting
confidence: 76%
“…Consequently the P-arm would not be properly positioned to stabilize a synapsiscompetent attR. Because Xis also promotes cooperative binding of Int at P2 (37)(38)(39), it seems likely that only low-affinity Int-attR interactions would be possible in its absence.…”
Section: Discussionmentioning
confidence: 99%
“…The Gateway technology is based on the bacteriophage lambda site-specific recombination system that facilitates the integration of lambda into the Escherichia coli chromosome (45). In the Gateway technology, the components of the lambda recombination system are modified to improve the specificity and efficiency of the system (46). Coding regions for viral (VARV-G1R, ECTV-002, MPXV-003, CPXV-006, and MYXV-M063) and human (NF-B1 and SKP1A) proteins were PCR amplified, using primers containing gene-specific sequences flanked by sequences representing modified components of the lambda recombination system (Table S3) and incorporated into pDNOR222 plasmid (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%